Music-based Language Programme for Preschool Teachers' Training and Lesson delivery : A Pilot Trial - Teena, Sim; Julia Ai Cheng, Lee (UNIMAS Publisher, 2023)
Language delay in preschoolers is linked to learning difficulties and persistent communication issues. Studies show that early music-making positively impacts young children's language development. Music-based Language Programme aims to enhance preschoolers’ language skills by training preschool teachers to deliver quality music lessons with language-focused objectives. This pilot trial aimed to determine the feasibility of teacher training for the programme's delivery. Furthermore, the secondary aim was to evaluate the acceptability of the programme's implementation by stakeholders. Methods: The 6-week one-arm pilot trial took place in Sarawak, Malaysia (October to November 2021). It included preschool visits, parent briefings, teacher training, and music lesson delivery. The participants included teachers (n = 4), preschoolers (n = 11), parents (n = 11), and the principal (n = 1) in a preschool that practiced inclusion. A non-probability-purposive sampling recruitment strategy was employed amid the COVID-19 pandemic. The study used a case study mixed methods approach to collect data through reports, observations, group discussions, feedback, questionnaires, and documentation. Results: There was a high rate of participant retention (100%) and completion of data collection tasks (91–100%). Additionally, there was a favourable shift (7–27%) in three teachers' self-efficacy ratings before and after the teacher training and a reasonably high implementation fidelity (87%). There were no adverse events related to the study participants. Conclusion: The study demonstrated promising results across multiple participant levels, as it was perceived to be feasible, acceptable, and appropriate by teachers, preschoolers, the principal, and parents. The findings provided direct implications for the progression of the pilot trial to the full-scale main study.